2013
DOI: 10.15665/rp.v11i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Adsorción por lote y en una columna de lecho fijo del colorante B39 sobre carbón activado granular

Abstract: Adsorción por lote y en una columna de lecho fijo del colorante B39 sobre carbón activado granularAdsorción por lote y en una columna de lecho fijo del colorante B39 sobre carbón activado granular Batch adsorption and fixed bed column of the B39 dye on granular activated carbon B39 RESUMEN Los colorantes están usualmente presentes en los efluentes acuosos de muchas industrias, como la textil, del cuero, el papel, la imprenta y cosméticos. La efectividad de la adsorción de colorantes presentes en aguas residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…The inverse relationship between the removal percentage and particle size is consistent with findings from several research studies, which have shown that a decrease in particle size leads to an increase in the superficial area [76]. This increase in superficial area facilitates the biosorption processes, which in turn improves the total removal efficiencies [77].…”
Section: Effect Of Particle Sizesupporting
confidence: 90%
“…The inverse relationship between the removal percentage and particle size is consistent with findings from several research studies, which have shown that a decrease in particle size leads to an increase in the superficial area [76]. This increase in superficial area facilitates the biosorption processes, which in turn improves the total removal efficiencies [77].…”
Section: Effect Of Particle Sizesupporting
confidence: 90%
“…This removal effect was a consequence of the chosen operating ranges, however, Hasan et al [17], reported that when using wider ranges (2 to 10 mL min -1 ) the influence of flow rate can be as high as 24.55%. In the study carried out by Valencia-Ríos and Castellar-Ortega [18], they obtained similar results, since from the point of view of column operation the best results were obtained at small flows, since the metallic ions had enough time to diffuse inside the activated carbon, improving their adsorption capacity. Abdolali et al [19], found that the increase in flow rate reduced the volume of effluent treated before bed was saturated and reduced bedtime and vice versa.…”
Section: Influence Of the Feed Ratementioning
confidence: 67%
“…Para determinar la capacidad de remoción del H2S y el tiempo de saturación [17] de todos los materiales sintetizados se realizaron mediciones en la entrada y salida del filtro que contenía los extrudados modificados, empleando tubos colorimétricos Gastec 4H y 4HH. En la medición se utilizó una bomba de aspiración Gastec GV-100-S-TR con capacidad para la aspiración de 50-100 mL.…”
Section: Determinación De La Capacidad De Remoción Del H2sunclassified